Analyzing Mass Housing Development User Satisfaction Maskane Mehr (Case Study: Mahshar Housing) - seyed jafar hejazi (توسعه اجتماعی)
Mass housing development identified as MaskaneMehr has been of the government’s major economic programs within the period of 2007-2013 in Iran. The government officials believed that their idea of excluding the land price from the total housing price and increasing the government role can resolve the housing need and meet the future demand for housing and decrease the consumer cost. As this program is regarded the biggest national plan and due to its importance, analyzing the effectiveness of this program is a vital decision. Therefore the main aim of this study is analyzing the housing occupants in Khuzestan province and particularly the city of Mahsahr, which has the largest number of housing development among other cities. The research method of this study is based on analytical-subjective and for the data collection analysis by the use of two methods of documentation and occupant’s view. The use of SPSS software and solidarity examining method with individual questioner forms has been chosen in order to achieve final analysis. The final results show that in the Mahshar housing development the degree of satisfactoryby the occupants is 2.83, which is considered as relatively good or medium. Other indexes and such as housing infrastructure, security, night light and ventilation are weak, while the most satisfaction are over the building quality and housing cost.